2018
DOI: 10.1073/pnas.1721203115
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring Yarrowia lipolytica toward triacetic acid lactone for materials generation

Abstract: Polyketides represent an extremely diverse class of secondary metabolites often explored for their bioactive traits. These molecules are also attractive building blocks for chemical catalysis and polymerization. However, the use of polyketides in larger scale chemistry applications is stymied by limited titers and yields from both microbial and chemical production. Here, we demonstrate that an oleaginous organism (specifically, ) can overcome such production limitations owing to a natural propensity for high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
151
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 38 publications
7
151
0
Order By: Relevance
“…The most successful strategy for triacetic acid lactone production deviated from traditional hosts and employed a precursor overexpression strategy in the non‐conventional yeast, Y. lipolytica . By overexpression of the pyruvate bypass pathway combined with ACC, this strain was able to generate 35.9 g L −1 of triacetic acid lactone in bioreactor fermentation . This result suggests that the oleaginous property of this yeast provides a more optimal starting point for acetyl‐CoA‐ and malonyl‐CoA‐derived polyketides.…”
Section: Acetyl and Malonyl‐coa Derived Polyketidesmentioning
confidence: 86%
See 4 more Smart Citations
“…The most successful strategy for triacetic acid lactone production deviated from traditional hosts and employed a precursor overexpression strategy in the non‐conventional yeast, Y. lipolytica . By overexpression of the pyruvate bypass pathway combined with ACC, this strain was able to generate 35.9 g L −1 of triacetic acid lactone in bioreactor fermentation . This result suggests that the oleaginous property of this yeast provides a more optimal starting point for acetyl‐CoA‐ and malonyl‐CoA‐derived polyketides.…”
Section: Acetyl and Malonyl‐coa Derived Polyketidesmentioning
confidence: 86%
“…It was recently shown that this high flux through acyl‐CoA precursors could be diverted away from lipid production and into production of the polyketide, triacetic acid lactone . While no other type III PKS‐derived polyketides have yet been produced by Y. lipolytica , the extraordinarily high titer achieved in this rewired strain holds promise as an exciting starting point for expanding the reach of this organism as a type III PKS‐derived polyketide host …”
Section: Microbial Hosts Considered For Heterologous Polyketide Produmentioning
confidence: 99%
See 3 more Smart Citations